Keanekaragaman jenis hasil hutan bukan kayu di Plot Permanen di Sungai Tapah, Jambi - Y. Purwanto; Eko Baroto Walujo; J. J. Afriastini (Journal of Tropical Ethnobiology, 2005)
Study on diversity of non timber forest products (NTFPs) in conservation area of PT Wirakarya Sakti represent the part of project research on "economic valuation of non timber forest products (N 1 FPs): multidisciplinary approach of biodiversity management". In this study, we established two permanent plots and each is 1 ha. We analyze of floristic diversity, identify useful plant species, non timber forest products diversity and study on ethnobotany of Malay society around the concession area of PT Wirakarya Sakti, Jambi. The study result of the tree composition which have diameter up to 10 cm in the permanent plot 1 ha, we accounted about 171 species of trees. The trees species which predominating this area is flydnocarpo polycephala, Parashorea aptera, PentaJpadon mot/9i, Pirmriodendron grrffitizi, Santiria rubi,ginosa, Argocarpms kr/mantic, Dysorylurn rit(gangi, Diazirms sp., Knema cinema, Nephelium maingaiii and NI. uncinatum, Shama spp., Syqygium, and others. The identification result of the useful plant species noted more than 300 plant species exploited by Malay society around the area. From a number of useful plant species which recognized by the society only about 5 % which used in their daily life as firewood, food, construction, equipments, medicinal, ritual and others. The NTFPs diversity which found in the permanent plot are fruits (35 species), vegetable (17 species), spices and flavor (6 species), cane and rattan (8 species), drug (> 35 species), poison (2 species), firewood (30-45 species), and honeybee (1 species).